Peningkatan Kesehatan dan Kemandirian Ekonomi Santri melalui Yogurt Sedot Sehat - Devi, Hilda Mazarina; Rosdiana, Yanti; Widyastuti, Fikka Kartika; Sujana, Indra Ahmad; Kitu, Graccelya Angel (Jurnal Abdimas Kesehatan (JAK), 2025)
A social welfare institution functions as a substitute for parents or guardians by fulfilling the physical, mental, and social needs of the children under its care, while also promoting activities that foster economic independence. A community service initiative, implemented through a series of workshops on the production of Healthy Squeezable Yogurt, was designed to strengthen partnerships that support both the health and economic sustainability of the institution. The program was conducted over a one-year period, with intensive mentoring provided for three months from July to September 2024 targeting caregivers and 55 residents of the Sunan Ampel Orphanage in Malang City. The mentoring sessions covered several key areas, including production, consumption, packaging, and marketing. After three months of implementation, 80% of the students were reported to consume yogurt regularly, while 91% experienced no health-related problems. Furthermore, the students demonstrated the ability to produce yogurt independently and accurately. It is recommended that the product packaging be further enhanced to increase its visual appeal, that marketing efforts be expanded through social media platforms, and that regular cooking shifts be established to promote the long-term business sustainability.